'The Revolution Is Not Over Yet' – German Speaking Ninth Graders' Conceptions Of The French Revolution. Issue 1 (1st November 2016) - Mathis, Christian
Abstract : This study applies the Model of Educational Reconstruction (MER) to history. A key assumption of the MER is that, by having a more intimate knowledge of the students' prior knowledge, the curriculum developer can create a curriculum content that can be taught in accordance with the learners' prior knowledge, i.e.the French Revolution and the second-order concept 'change/ continuity'. Three areas of research are being addressed; Firstly, a hermeneutical analysis of the content structure and the concepts behind it make it possible to clarify scientifically the subject matter, i.e.the scientific clarification; Secondly, empirical investigations of the learners' conceptions concerning the subject matter, allow for a better comprehension of the students' perspectives. Thirdly, in educational structuring, the structure of the subject matter is gained by relating the students' conceptions with the scientific concepts; The empirical data is gathered from German-speaking Swiss 9th-graders (N=22) by the means of group discussions and problem-centred interviews. The data has been evaluated using a reconstructive qualitative method. Twelve typical patterns of explanation have been reconstructed, e.g.'order and stability' or 'freedom of expressing opinions'. These patterns of explanation are constructed in an everyday sense and not according to academic history. A super-pattern called 'presentism' could be isolated which interferes with all other patterns, thus obstructing the students' academic historical thinking. One consequence is that teachers should act as cognitive models and guide their students with purposeful scaffolding to proper historical thinking which avoids presentism.